GEOGRAPHICAL ASPECTS OF STUDYING THE NATURE AND ECONOMIC FEATURES OF THE ASAKA DISTRICT OF THE ANDIJAN REGION - Abdullaev Ilkhom Khatamovich; Komiljonova Mokhinur Murodjon's Qizi (Western European Studies, 2023)
The article discusses issues of geography and development of the automotive industry in Uzbekistan. In particular, the history of the development of the automotive industry and its role in the regional economy, the geography of production and export of cars in Uzbekistan are given
Keywords: areas; Uzbekistan; geography; automotive